Pengaruh Gas Yang Terjebak Pada Liquid Di Micromotion Terhadap Productivity Index - Eko Prastio; Wahyu Sutresno; Tania Stivani Pangestu (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2024)
The exploitation of oil and gas requires accurate and real-time measurements to ensure operational effectiveness and optimal production results. Surface well testing is one method used to assess well performance in producing oil and gas, as well as to evaluate the stability and efficiency of surface operations. In surface well testing, the use of a Multiphase Flow Meter (MPFM) with Micromotion sensors to measure liquid flow (oil and water) and Vortex sensors to measure gas flow is essential. This study aims to evaluate the impact of gas that gets trapped and tested by the Micromotion sensor on the Productivity Index (PI) of production wells. Data was obtained from real-time well test reports from PT. Mitra Prana Abadi Sentosa, which included water cut, drive gain, gas velocity, density, and various other well test data. Data collection techniques included field studies using quantitative methods to calculate the PI of the tested wells, as well as literature reviews to obtain secondary data supporting the theoretical foundation. Data was analyzed by filtering and categorizing according to research needs. The presence of trapped gas in the liquid flow affects the well’s PI. A high drive gain value indicates a decrease in the well’s production efficiency.